Efektivitas Strategi Pembelajaran Kolaboratif Berbasis Pedagogik dalam Meningkatkan Keterampilan Sosial Siswa - Muhammad Rahmadani; Attari Khul Kabir; Hendra Kurniawan; M. Dwi Aulia Akbar; Muhammad Nasir (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the effectiveness of a pedagogically grounded collaborative learning strategy in enhancing students’ social skills, addressing the growing concern over limited interpersonal competencies in contemporary classroom settings. The research seeks to answer how and to what extent collaborative pedagogical approaches contribute to the development of students’ social interaction, communication, and cooperation abilities. Employing a quasi-experimental design with a mixed-method approach, data were collected through observations, questionnaires, and structured interviews involving secondary school students. The findings indicate a significant improvement in students’ social skills, particularly in aspects of teamwork, empathy, and active participation, as evidenced by increased engagement levels and positive behavioral changes during collaborative activities. The integration of pedagogical principles within collaborative learning not only facilitates cognitive achievement but also fosters meaningful social interaction among learners. The study concludes that pedagogically driven collaborative strategies serve as an effective instructional model for cultivating students’ social competencies, suggesting their broader implementation in educational practice to support holistic student development.